Pretreatment of Cellulose from Sugarcane Bagasse with Xylanase for Improving Dyeability with Natural Dyes - Senapitakkul, Viradee (ACS Omega, 2020)
[Image: see text] In this study, cellulose was obtained from sugarcane bagasse (SCB) and treated with xylanase to remove residual noncellulosic polymers (hemicellulose and lignin) to improve its dyeability. The cellulose fibers were dyed with natural dye solutions extracted from the heart wood of Ceasalpinia sappan Linn. and Artocarpus heterophyllus Lam. Fourier-transform infrared (FTIR) spectroscopy, Raman analysis, and whiteness index (WI) indicated successful extraction of cellulose by eliminating hemicellulose and lignin. The FTIR analysis of the dyed fibers confirmed successful interaction between natural dyes and cellulose fibers. The absorption (K) and scattering (S) coefficient (K/S) values of the dyed fibers increased in cellulose treated with xylanase before dyeing. Scanning electron microscopy (SEM) analysis showed that the surface of alkaline-bleached fibers (AB-fibers) was smoother than alkaline-bleached xylanase fibers (ABX-fibers), and the presence of dye particles on the surface of dyed fibers was confirmed by energy-dispersive spectrometry (EDS) analysis. The X-ray diffraction (XRD) revealed a higher crystallinity index (CrI), and thermal gravimetric analysis (TGA) also presented higher thermal stability in the dyed fibers with good colorfastness to light. Therefore, xylanase treatment and natural dyes can enhance dyeability and improve the properties of cellulose for various industrial applications.